Goaf Gas Control Improvement by Optimizing the Adjacent Roadway Large-Diameter Boreholes. (22nd July 2021) - Wang, Wei; Li, Zongxiang; Yu, Hongming
Abstract : This study introduced gas control technology in goaf using adjacent roadway large-diameter (550 mm) boreholes to control gas accumulation in the upper corner of a fully mechanized working face in high-gas coal seams. The gas control process in the upper corner and gas interception in goaf by large-diameter boreholes was analyzed using the CFD model of the gas flow in goaf. The latter considered the control equation of gas flow, the established permeability model of goaf, and the gas emission law in goaf. Using the 2-105 working face of the Tenghui Coal Mine, Shanxi Province, China, as a case study, the distribution patterns of gas concentration and flow field in the goaf for various extraction flow parameters and different positions of boreholes were numerically simulated. The dependences between various locations, drainage flows, and the gas concentration in the upper corner were determined and fitted by engineering equations. The evolution pattern of the spontaneous combustion zone in the goaf under the drainage conditions was also analyzed. The optimal borehole configuration parameters ensuring the extraction flow rate exceeding 3 m·s −1 and the effective gas control in the upper corner of the working face at a distance of 5 m–15 m behind the working face were identified. The engineering practice proved the feasibility of gas control in the goaf using the adjacent roadway large-diameter borehole. The gas concentrations in the return airflow and the upper corner of the working face were kept below 0.65 and 0.8%, respectively, to ensure production safety and improve the gas utilization efficiency.